Netting Gut Disease: Neutrophil Extracellular Trap in Intestinal Pathology. (19th October 2021) - Chen, Kai; Shao, Li-Hua; Wang, Feng; Shen, Xiao-Fei; Xia, Xue-Feng; Kang, Xing; Song, Peng; Wang, Meng; Lu, Xiao-Feng; Wang, Chao; Hu, Qiong-Yuan; Liu, Song; et al.
Abstract : Many gut disease etiologies are attributed to the presence of robust inflammatory cell recruitment. The recruitment of neutrophils plays a vital role in inflammatory infiltration. Neutrophils have various antimicrobial effector mechanisms, including phagocytosis, oxidative burst, and degranulation. It is suggested that neutrophils could release neutrophil extracellular traps (NETs) to kill pathogens. However, recent evidence indicates that neutrophil infiltration within the gut is associated with disrupted local immunological microenvironment and impaired epithelial barrier. Growing evidence implies that NETs are involved in the progression of many diseases, including cancer, diabetes, thrombosis, and autoimmune disease. Increased NET formation was found in acute or chronic conditions, including infection, sterile inflammation, cancer, and ischemia/reperfusion injury (IRI). Here, we present a comprehensive review of recent advances in the understanding of NETs, focusing on their effects in gut disease. We also discuss NETs as a potential therapeutic target in gut disease.